2013
DOI: 10.1136/acupmed-2012-010269
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Acupuncture on the Outcomes of in Vitro Fertilisation When Embryo Implantation Has Failed: A Prospective Randomised Controlled Clinical Trial

Abstract: Objective To evaluate the effectiveness of acupuncture and moxibustion as an adjuvant treatment in women undergoing in vitro fertilisation (IVF) when embryo implantation has failed. Methods A prospective, randomised controlled clinical trial was conducted with 84 infertile patients who had had at least two unsuccessful attempts of IVF. The patients were randomised in three groups: control (n=28), sham (n=28) and acupuncture (n=28). The sample size was calculated by assuming a pregnancy rate of 10% when embryo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 29 publications
0
41
0
2
Order By: Relevance
“…The characteristics of the included trials are summarized in table 2. Acupuncture at follicle phase only was used in 2 of the trials [29,30], while the other 2 trials used acupuncture at follicle phase and around ET [31,32]. All 4 trials were published as full reports - 1 in the UK [31], 1 in Australia [32] and 2 in China [29,30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the included trials are summarized in table 2. Acupuncture at follicle phase only was used in 2 of the trials [29,30], while the other 2 trials used acupuncture at follicle phase and around ET [31,32]. All 4 trials were published as full reports - 1 in the UK [31], 1 in Australia [32] and 2 in China [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…Brenner [40] stated that this is a widespread issue with acupuncture trials as a one-size-fits-all protocol; these trials only give information on that protocol and not on the possibility of success with acupuncture. In the study of di Villahermosa et al [31], acupuncture was performed on the 1st and 7th day of ovulation induction, on the day before ovarian puncture and on the day after ET. The study showed that the CPR in the acupuncture group was significantly higher than that in the control and sham groups.…”
Section: Discussionmentioning
confidence: 99%
“…6 7 Successful implantation depends on a synchronised dialogue between high quality blastocysts and a receptive endometrium. 8 Different strategies have been developed to assess endometrial receptivity including measurement of endometrial cytokines and ultrasound examination. The HOXA10 gene codes for a transcription factor that functions as a regulator of uterine organogenesis during the embryonic period.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this assumption, acupuncture has been shown to increase endometrial thickness compared with sham acupuncture and standard care. 44 However, Shuai et al 48 are the first to have shown positive effects on contemporary ultrasound markers of endometrial receptivity (three-dimensional endometrial and subendometrial vascularisation index and presence of a triple-line pattern) plus HOXA10 protein expression, a novel molecular marker. Interestingly, all these studies have used serial treatments that incorporate the follicular phase of the cycle.…”
mentioning
confidence: 99%